A consolidação da romaria do Caaró a partir da mídia impressa, 1937-1945 - Marin, Diosen (2014)
This study is related to the research line Integração, Política e Fronteira of the Post-graduation Program in History of the Federal University of Santa Maria, I went colleger CAPES. He dedicated to analyze the approximation between Getúlio Vargas governments and the Catholic Church, during the 1937 and 1945 and why relationship enable the consolidation of Romaria do Caaró when establish the linking of past, in other words, when recollect the life, work and death of priests Roque González, Alonso Rodríguez e Juan del Castillo. For the research we propose a content analysis of publications printed in the Catholic and secular media of Rio Grande do Sul, respectively in Rainha dos Apóstolos , UNITAS: Revista Eclesiástica da Arquidiocese de Porto Alegre , Revista do Instituto Histórico e Geográfico do Rio Grande do Sul magazines and A Notícia newspaper, aticulated between 1937 and 1945 years. Throughout the study, it was realized that the Romaria do Caaró consolidation dependent of any contextual factors as aproximated of Estate end Catholic Church and discussion about the construction of Nation and Nationalism of country, and local elements that understand the Roque González passage on Rio Grande do Sul (1940) and the 4º Centenary of the Society of Jesus celebrations (1940). So, despite the signaled that Romaria do Caaró were the local history, it is inserted into a bigger picture.